Efficiency Evaluation and Projection Improvement of the Industrial Water–Energy Nexus in China Based on Network Data Envelopment Analysis - Liang, Shizhi; Huang, Yufei; Ding, Tao (Frontiers in Energy Research, 2021)
Water and energy are critical resources for human well-being. The quantification and explanation of water-energy nexus is important to enrich our understanding of sustainable utilization of water and energy resources in a unified framework. Herein, from the perspective of production efficiency, this study investigates the water-energy nexus in China’s industrial sector by developing a network data envelopment analysis (DEA) approach. Under two practical principles, we evaluate the water and energy usage efficiencies as well as give projection points in terms of industrial production and wastewater treatment processes for 30 provinces or urbans in China during 2011-2015. The results show that the overall efficiency values of most provinces in industrial water-energy nexus system are high although the efficiency value of each province fluctuations up and down in the sample period. When comparing two sub-systems, for most provinces, the sub-efficiencies of industrial production sub-system are relatively higher than that of wastewater treatment sub-system under whether economic priority principle or environment priority principle. Considering the projection points, the potential improvement space of the environment priority strategy is higher than that of the economic priority strategy. Based on the empirical results, relevant policy suggestions are provided to improve provincial or urban industrial water-energy nexus system in reality.